Application Necessity of Gas Radiant Heating Systems for Industrial Objects - A. Y. Gladkov; E. G. Migoutski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
The paper considers a possibility and justification to use gas systems for heating industrial buildings due to radiant heating.  Heating modes of heat systems are given in the paper.